O perfil dos gerentes do Banco Central do Brasil: tradicionalismo ou contemporaneidade aberta do futuro? - Magalhães, Ana Maria Brandão (2001)
The objective ofthis dissertation is to investigate whether the profile ofthe Central Bank's managers presents some features that make way for their performances in accordance to contemporary management concepts, which are: more flexibility, decentralization of decisions empowerment, delegation, participation, creativity, innovation, susceptibility to changes, administrative rationality, investment in the functional corps valuation, more transparent/communicative management, or, on the other hand, if concepts of a more traditional, weberian management still perdure, such as centralization, technically oriented management, hierarchic authority, verticality, impersonality, standardization of methods and procedures. Bibliographic and documentary researches have been carried through in order to base the concepts of the relations between theoretical and practical management in the Central Bank. The features of the managers's profile have been determined through interviews with Central Bank's President and Directors, as well as through questionnaires addressed to managers and their subordinates. This process allowed us to analyze the management in the Central Bank through three leveIs: board of directors, managerial team and operational corps. Although the Central Bank's managers present a trend to the traditional management the results of the study demonstrate that their subordinates perceive themselves being at a transitional moment, which reflects a paradigm change, while they absorb new concepts of contemporary management. This whole transition is guaranteed by the Upper Management.